Platformed Sex Lives - Sundén Jenny; Tiidenberg Katrin; Paasonen Susanna (United States, 2026)
This panel builds on a recently funded research project on the geopolitics of digital sexual cultures in Estonia, Sweden, and Finland (2020-2022) investigating three local online platforms devoted to communities around nudity and kink: iha.ee, darkside.se, and alastonsuomi.com. Our case studies are in a sense “edge cases” which partly move within sexual margins, making space for alternate understandings of platform sociability. Contra to the current de-platforming of sex, our case-studies foreground sex as the dynamics that bind users to the sites and fuel diverse engagements between them. The papers are work in progress and provide initial platform analyses inspired by the walkthrough method (Light et al. 2018) and the notion of platforms as microsystems (van Dijck 2013). We focus on platform affordances and governance in terms of gender and sexuality; acceptable behavior and sexual practices; and public visibility and privacy. This opens up three important discussions with relevance to the AoIR community: (1) how digital platforms shape and constrain sexual expression at a political moment when the sexual dimensions of life are increasingly pushed out of public view; (2) how these local platforms, as notable arenas for sexual expression, contribute to sexual cultures within the Nordic and Baltic region; and (3) how our examples, when understood as social media platforms, can help to push understandings of what social media are, how they operate, and what kind of sociability they allow for. The panel opens up a discussion of how sex matters in social media, how it is valued and communicated.